Robotic Knee Prosthesis with Cycloidal Gear and Four-Bar Mechanism Optimized Using Particle Swarm Algorithm - Al Kouzbary M.; Al Kouzbary H.; Liu J.; Khamis T.; Al-Hashimi Z.; Shasmin H.N.; Arifin N.; Abu Osman N.A. (MDPI, 2023)
A powered transfemoral prosthesis is needed as people with transfemoral amputation show 60 percent extra metabolic cost when compared to people with no amputation. Recently, as illustrated in the literature, the most high-torque robotic knee prosthesis utilize harmonic reducers. Despite the advantage of high reduction ratio and efficiency, the harmonic drive cannot be back-driven. Therefore, the harmonic drive is not an optimal solution for prosthetic systems with direct and indirect contact with the environment. In this paper, we outline an initial design of robotic knee prosthesis. The proposed robotic knee prosthesis consists of BLDC motor, cycloidal gear with reduction ratio 13:1, four-bar mechanism, and timing belt transmission with 4:1 reduction ratio. To optimize the torque transmission and range of motion (RoM), a multiobjective optimization problem must be undertaken. The end-effector motion depends on each bar length in the four-bar mechanism. The four-bar mechanism was optimized using particle swarm optimization (PSO). To complete the optimization, a set of 50 steps was collected using wearable sensors. Then, the data of sagittal plan were processed to identify the target profile for PSO. The prototypes computer-aided manufacturing (CAM) was completed using a MarkTwo 3D printer with carbon fiber composite. The overall design can achieve a maximum torque of 84 N.m. However, the current design lacks the elastic component (no spring is added on the actuator output), which is necessary for a functional prosthesis; this limitation will be addressed in future study. 2022 by the authors.